Pembelajaran Bahasa Bahasa Asing dan Tolerance of Ambiguity: Sebuah Studi Kasus dari penguasaan Grammar - Dudung Gumilar; Syihabudin Syihabudin (Jurnal Studi Guru dan Pembelajaran, 2023)
Tolerance for Ambiguity (TfA) which is commonly involved in the field of Human Resources in industry has been adopted in the development of the quality of foreign language learning, especially foreign language acquisition by learners. In this study, the reference is French language which is limited by Subject Verb Agreement involving the periodic verb [+Present]. There are two research objectives, namely (1) to describe the tendency of TfA level at the beginning of the lecture and (3) to describe the students' efforts in developing TfA. The results of the study using a qualitative descriptive approach show that, first, the students have a high level of TfA although the students still make mistakes in French but the problem is not too significant because the suffixes representing the features of Tense [+Present], Person [+1P, +2P, +3P] and Number [±Plural] on verbs from the grammar area Subject Verb Agreement (SVA). Secondly, a high level of TfA is well-established by the students because they have the ability to maintain and develop the aspect of efforts to master SVA in French.